Are Foreign Aid and Remittance Inflows a Hedge Against Food Price Shocks?. (IMF Working Papers; Working Paper, 2012)
This paper explores the role of foreign aid and remittance inflows in the mitigation of the effects of food price shocks. Using a large sample of developing countries and mobilising dynamic panel data specifications, the econometric results yield two important findings. First, remittance and aid inflows significantly dampen the effect of food price shocks in the most vulnerable countries. Second, a lower remittance-to-GDP ratio is required in order to fully absorb the effects of food price shocks compared to the corresponding aid-to-GDP ratio.